Comparative study on the blood physiological, biochemical indexes and liver histology of Schizothorax wangchiachii (♀), Percocypris pingi (♂) and their hybrids - Huang, Jiange; Zhuo, Dayou; Wang, Mengyao; Yeerda, Saiqin; Huang, Jiajun; Qin, Xiaofeng; Lu, Minfang; Wang, Zhijian; Liu, Xiaohong (Frontiers in Marine Science, 2024)
Previous studies have shown that, hybrids derived from the cross between Schizothorax wangchiachii (♀) and Percocypris pingi (♂) are significantly different from their parents in terms of growth performance, feeding behavior and disease resistance. Both cellular and plasma components of blood are integral to immune system, and erythrocytes serve as the sole cells for transporting oxygen which makes energy available for the growth, development, immune responses and all other physiological activities. In order to understand ecological adaptive strategies and also the underlying physiological and biochemical mechanisms of fish with different characteristics, offsprings and hybrids produced by artificial reproduction of the same batch of domesticated S. wangchiachii, P. pingi broodstock were selected, and analyses of biochemical indexes, differential leucocytes counts and histological examination of liver were performed. Results showed that the proportion of lymphocytes and thrombocytes in P. pingi was significantly higher than that in S. wangchiachii (P<0.05). In contrast, all blood cell values of hybrids fell between those of its parent species, with the exception of the percentage of thrombocytes, which was the highest of the three. The erythrocyte area, perimeter and short diameter of hybrid fish were significantly higher than those of S. wangchiachii and P. pingi (P<0.0001), while P. pingi exhibited the smallest erythrocyte values. Hepatocyte area, perimeter and short diameter were also significantly higher in hybrids than in S. wangchiachii and P. pingi, and P. pingi had the smallest values. The number of Kupffer cells per unit area of liver was significantly greater in S. wangchiachii than in hybrids and Percocypris pingi (P<0.05). Plasma C-reactive protein level was nearly undetectable in S. wangchiachii, but it could reach 10 mg/L in both P. pingi and hybrids. Besides, plasma total bile acids was significantly higher in S. wangchiachii than in P. pingi (P<0.01), and hybrids fell in intermediate level. These results suggest that there may be differences in the immune functions among these three fish, as well as in their liver metabolism and protein synthesis capabilities. These findings here might provide some crucial clues in understanding the biodiversity and fish adaptation, further promote the development of wild fish cultivation.